2020
DOI: 10.3389/fphar.2020.00758
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimethamine Elicits Antitumor Effects on Prostate Cancer by Inhibiting the p38-NF-κB Pathway

Abstract: Since incurable castration-resistant prostate cancer (CRPC) inevitably develops following treatment with androgen deprivation therapy, there is an urgent need to devise new therapeutic strategies to treat this cancer. Pyrimethamine, an FDA-approved antimalarial drug, is known to exert an antitumor activity in various types of human cancer cells. However, whether pyrimethamine can inhibit prostate cancer is not well established. Hence, the present study aimed to characterize the mechanism of action of pyrimetha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…Pyrimethamine is known as an antifolate drug that blocks the parasitic dihydrofolate reductase (DHFR), which is essential for DNA and RNA synthesis. Recently it was reported that pyrimethamine can inhibit DHFR, thymidine phosphorylase (TP) [77], p38protein [78] and STAT3 transcriptional activity [79, 80] in human cells. The polypharmacological profiles of chloroquine and pyrimethamine motivated us to check their effect on the hRSV-A polymerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrimethamine is known as an antifolate drug that blocks the parasitic dihydrofolate reductase (DHFR), which is essential for DNA and RNA synthesis. Recently it was reported that pyrimethamine can inhibit DHFR, thymidine phosphorylase (TP) [77], p38protein [78] and STAT3 transcriptional activity [79, 80] in human cells. The polypharmacological profiles of chloroquine and pyrimethamine motivated us to check their effect on the hRSV-A polymerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have been shown to be safe in humans because they inhibit STAT3 at concentrations routinely achieved in human plasma ( Khan et al, 2018 ; Takakura et al, 2011 ; Xiang et al, 2016 ). To our knowledge, PYR and AQ have yet to be specifically assessed in endothelium, as prior studies have primarily evaluated their STAT3 inhibitory effects on tumor cells of epithelial origin ( Cheng et al, 2020 ; Coates et al, 2020 ; Khan et al, 2018 ; Lin et al, 2018 ; Liu et al, 2019a , b ; Wu et al, 2020 ; Xiang et al, 2016 ; Zhou et al, 2020 ). Therefore, we first treated HUVECs with various concentrations of PYR or AQ for different durations to determine the optimal conditions, while not exceeding the concentrations typically achieved in human plasma ( …”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al evaluated the potency of pyrimethamine against CRPC (DU145 and PC3) cells. Pyrimethamine significantly reduced the viability, induced the cell cycle arrest in the S‐phase, and promoted the apoptosis of CRPC cells 84 . The proapoptotic effect of pyrimethamine was evidenced by the decrease in the expression of antiapoptotic proteins (such as Bcl‐2 and Bcl‐xL).…”
Section: Antineoplastic Effects Of Pyrimethaminementioning
confidence: 99%